Pengaruh Atribut Produk, Penetapan Harga dan Media Sosial Terhadap Keputusan Pembelian pada Nolan Jersey Pekanbaru - Alfian Rizqy Mauliddin; Mashur Fadli (Peneliti.net, 2023)
This study aims to determine the effect of product attributes, pricing and social media on purchase decisions at Nolan Jersey Pekanbaru. The method used in this research is descriptive and quantitative statistics using explanatory research models. The sample in this study amounted to 100 respondents who were determined using accidental sampling and using a questionnaire for data collection techniques. From data analysis with measurement models, structural models and hypothesis testing, the results show that product attributes have a positive and significant effect on purchasing decisions with a path value of 0.000 <0.05 and t-statistic 5,077 > 1.96, pricing has a positive and significant effect on decisions purchases with a path value of 0.005 <0.05 and t-statistic 2,845 > 1.96, and social media has a positive and significant effect on purchasing decisions with a path value of 0.000 <0.05 and t-statistic 4,447 > 1.96.